Gas Hydrate Stability Zone of the Barents Sea and Kara Sea Region. (November 2016) - Klitzke, Peter; Luzi-Helbing, Manja; Schicks, Judith M.; Cacace, Mauro; Jacquey, Antoine B.; Sippel, Judith; Scheck-Wenderoth, Magdalena; Faleide, Jan Inge
Abstract: In this study we assess the present-day gas hydrate stability zone for the Barents Sea and Kara Sea region. Thereby, we make use of a data-based 3D lithosphere-scale pressure and thermal model. The resulting gas hydrate stability zone varies within >1km across the study area and strongly correlates with the local geological settings and the corresponding geothermal gradient. Gas hydrates containing hydrocarbons from a thermogenic source (CH4 +C2 H3 +C3 H8 ) are potentially more widespread than previously assumed. The corresponding thermogenic feed gas may have derived from leaking petroleum systems during late Cenozoic basin inversion.